Factors influencing brand recognition: a case of Prudential BSN Takaful Berhad / Zakaria Mat Zin, Noorliyana Zakaria and Intan Nadia Othman - Mat Zin, Zakaria; Zakaria, Noorliyana; Othman, Intan Nadia (Arshad Ayub Graduate Business School, 2018)
The focus of this study is on Prudential BSN Takaful Berhad (PruBSN) in understanding the influence of brand recognition. There is another insurance company that carries ‘Prudential’ as part of its company name which is Prudential Assurance Malaysia Berhad (PAMB). Since there are two insurance companies carrying the same prominent name, there is a brand confusion issue among the policyholders or customers.. This brand confusion has caused a negative impact on PruBSN. The purpose of this study is to assist PruBSN to overcome the issue of this brand confusion by looking at the factors that influence brand recognition. The research framework has been constructed with three postulated independent variables (IVs) on brand recognition.. The objectives of the study were to study the relationship between product knowledge, product innovation and brand experience as the IVs, towards brand recognition and to determine the strength of each variables on brand recognition. To achieve this, correlation and regression analysis were conducted using SPSS, the statistical analysis software. The researchers have also used SWOT analysis to study the situational analysis of PruBSN. Some recommendations were developed based on the SWOT and TOWS analyses. Using a quantitative method of survey to gather the data, an online data collection process ensued. The researchers managed to collect 120 completed responses. The study concludes that only brand experience has the strongest influence on brand recognition